Career Development Based Transformational Leadership, Education & Training, and Motivation (Case Study at Dinas Lingkungan Hidup and Kebersihan Kota Kupang) - Jefirstson Richset Riwukore; Tien Yustini; Markus Tada (Enrichment : Journal of Management, 2022)
The purpose of the study was specifically to obtain the results of the analysis of the effect of transformational leadership, education & training and motivation partially or simultaneously. The research method uses descriptive and verification surveys, and field data collection uses questionnaires, interviews, and documentation techniques. This research is associative research, where in this study there are variables that are related and can influence other variables. The research population was 164 employees who were determined by saturated samples for the determination of respondents so that the entire population became the research sample. Processing data using SPSS 25 analysis tools. The results of this study indicate that the variables of commitment and compensation have a positive and significant effect on performance, while work ethic has no and no significant effect on performance. The results of this study indicate that transformational leadership and education & training have a positive and significant effect on career development, while motivation has a negative influence on career development. Simultaneously, the predictors of career development consist of transformational leadership, education & training, and motivation.